2017
DOI: 10.20960/nh.975
|View full text |Cite
|
Sign up to set email alerts
|

Asociación de la percepción materna del peso del hijo y estilos maternos de alimentación infantil

Abstract: Introduction: Mothers do not recognize when their child is overweight or obese (OW-OB), and the evidence suggests a relationship between inadequate maternal perception of her child weight (MPCW), and maternal feeding style (MFS). Objectives: a) To assess the reliability of the Caregiver Feeding Style Questionnaire (CFSQ); b) to verify association between MPCW and child' nutritional status; c) to describe the MFS; d) to verify differences between MPCW and child's body mass index (BMI); e) and to verify the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
1
13
0
3
Order By: Relevance
“…The results for validity of body weight perception in children’s parents were similar to those found in studies in Mexico ( 34 ) and Puerto Rico ( 35 ) , confirming there is low validity between parents’ perception of their child’s weight and the child’s real BMI ( κ =0·164, Kendall’s τ c =0·124). Similar reports were presented by other studies from Chile ( 36 ) and Mexico ( 37 ) , where the authors concluded that parents of children with overweight have a distorted body image of them and tend to perceive them to be thinner than they really are. In the study from Mexico, it was also found that only a small proportion of mothers of children with overweight or obesity were able to perceive their child’s weight correctly.…”
Section: Discussionsupporting
confidence: 86%
“…The results for validity of body weight perception in children’s parents were similar to those found in studies in Mexico ( 34 ) and Puerto Rico ( 35 ) , confirming there is low validity between parents’ perception of their child’s weight and the child’s real BMI ( κ =0·164, Kendall’s τ c =0·124). Similar reports were presented by other studies from Chile ( 36 ) and Mexico ( 37 ) , where the authors concluded that parents of children with overweight have a distorted body image of them and tend to perceive them to be thinner than they really are. In the study from Mexico, it was also found that only a small proportion of mothers of children with overweight or obesity were able to perceive their child’s weight correctly.…”
Section: Discussionsupporting
confidence: 86%
“…It was also identified that the highest average value of DS was found in the authoritarian MCFS and it was found that the dimension of demandingness is a determining factor of the DS. This finding is considered important given that, as indicated above, the literature documents that the MCFS that predominates among Hispanic mothers is the indulgent (Hidalgo-Mendez et al, 2019) while in Mexican mothers the authoritarian style predominates (Flores-Peña et al, 2017), which is characterized by controlling, managing limits and strict rules, which could lead mothers to a high level of stress and anxiety, seeing that their demands are not met, and therefore, they are more likely to cause depressive disorders.…”
Section: Discussionmentioning
confidence: 84%
“…It result should be noted that it is available in 11 languages with good psychometric properties, high internal consistency, and convergent validity; it is considered that the CESD-R is an overall accurate and valid depression measure in general and it is available online (Van Dam & Earleywine, 2011). On the other hand, the Caregiver Eating Styles Questionnaire showed acceptable internal consistency; this questionnaire has been applied to Hispanic mothers living in the United States and to Mexican mothers as well (Flores-Peña et al, 2017;Hughes et al, 2005) and has shown acceptable internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, el que las madres se enfoquen en el tipo de práctica dependiendo del peso de sus hijos es contraproducente, pues se ha encontrado que las madres de hijos preescolares con sobrepeso y obesidad no perciben que su hijo tiene esta condición; ejercen un estilo de alimentación "no involucrado o indiferente" y en niños con peso normal ejercen un estilo autoritario, que ambos son denominados estilos de crianza en la alimentación (Flores-Peña et al, 2017).…”
Section: Introductionunclassified